Navigating Occupational Hazards: Musculoskeletal Disorders Among Slaughterhouse Workers in Brazil - Vando Aparecido Monteiro; Hercules Jose Marzoque; Marcelo Linon Batista; Maria do Carmo Baracho de Alencar; Lilian Dias Pereira; Irenilza de Alencar Nääs (Safety)
(1) Background: The meatpacking industry in Brazil is vital for economic growth. It poses significant occupational health risks, particularly Work-Related Musculoskeletal Disorders (WMSDs). The present study analyzes the profile of slaughterhouse workers based on the governmental notification database. (2) Methods: The socio-demographic dataset (n = 820) was filled with worker data, and health profiles reported Repetitive Strain Injuries (RSI) and WMSDs from 2007 to 2019, available online by the Brazilian Health Service. The dataset was analyzed to identify patterns of injuries and contributing factors. Descriptive statistics outlined worker characteristics, while Analysis of Variance (ANOVA) explored associations between variables. (3) Results: The results revealed that 51.34% of workers were male, with most aged 30–45. Repetitive movements were reported by 89.63% of respondents, while 78.90% worked shifts exceeding six hours. Soft tissue disorders were the most prevalent diagnosis (40.97%). The majority (53.17%) experienced temporary disabilities, and 5.73% had permanent impairments. Key risk factors included inadequate breaks, stressful environments, and limited ergonomic adaptations. This study highlights the critical need for preventative measures, such as ergonomic interventions, adequate rest breaks, and employee education, to mitigate WMSDs. Future research should include ergonomic evaluations and consider broader organizational variables to enhance slaughterhouse occupational health and safety. Addressing these challenges is essential for improving worker welfare and maintaining industry productivity.